Applying developmental science concepts to improve the applicability of children's food preference learning research. (18th April 2022) - Anzman‐Frasca, Stephanie; Moding, Kameron J.; Forestell, Catherine A.; Francis, Lori A.
Abstract: In many nations today, the quality of children's diets is low, with numerous children rejecting healthy foods. Fortunately, young children can learn to like and consume new and previously rejected foods with experience, as evidenced by extensive experimental research. In this article, we propose integrating research on children's food preference learning with concepts from developmental science to facilitate generalizability across a wider range of children's characteristics and environments. We review emerging research suggesting that increased consideration of individual differences in responsiveness to food preference learning strategies and ecological validity can facilitate dissemination of evidence‐based feeding strategies that fit various children's characteristics and contexts. We incorporate Gottlieb's theory of probabilistic epigenesis to illustrate the importance of considering both individual differences in constitutionally based characteristics and children's naturalistic eating environments since these continually act together to affect eating outcomes. Further research incorporating these factors can help a broader population of parents and caregivers encourage healthy eating in young children's everyday environments.